2014
DOI: 10.15252/emmm.201303698
|View full text |Cite
|
Sign up to set email alerts
|

Biology, detection, and clinical implications of circulating tumor cells

Abstract: Cancer metastasis is the main cause of cancer-related death, and dissemination of tumor cells through the blood circulation is an important intermediate step that also exemplifies the switch from localized to systemic disease. Early detection and characterization of circulating tumor cells (CTCs) is therefore important as a general strategy to monitor and prevent the development of overt metastatic disease. Furthermore, sequential analysis of CTCs can provide clinically relevant information on the effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
488
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(495 citation statements)
references
References 112 publications
4
488
0
3
Order By: Relevance
“…The numbers of cancer cells shed by tumours into the bloodstream may be exceedingly low, and the biological and clinical relevance of CTCs in sustaining malignant disease has been questioned 40 . However, as CTCs are shed by tumours on a stochastic rather than a deterministic basis 41 , they are expected to better recapitulate the distribution of different subclonal tumour populations (TABLE 1).…”
Section: Modelling Cancer Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…The numbers of cancer cells shed by tumours into the bloodstream may be exceedingly low, and the biological and clinical relevance of CTCs in sustaining malignant disease has been questioned 40 . However, as CTCs are shed by tumours on a stochastic rather than a deterministic basis 41 , they are expected to better recapitulate the distribution of different subclonal tumour populations (TABLE 1).…”
Section: Modelling Cancer Phenotypesmentioning
confidence: 99%
“…As mentioned above, a step forwards for minimally invasive tumour sampling is the isolation and characterization of CTCs, detected at low concentrations in the peripheral blood of patients with different solid tumours 40 . Although the role of CTCs in metastasis development is still uncertain 40 , their levels ostensibly correlate with patient survival and response to therapy [94][95][96] . These features mean that CTCs are promising tools to monitor cancer burden and drug susceptibility in metastatic and late-stage disease, when repetitive biopsies are not indicated.…”
Section: Modelling Metastatic Disease Subcutaneous Transplantation Umentioning
confidence: 99%
“…However, determinations of serum CHI3L1 in cancer patients may be not tumor-specific due to secretion from inflamed normal tissues. High expression of CHI3L1 in solid tumors, as indicator of dissemination and poor prognosis, may at least partially be due to CHI3L1-positive CTCs (109).…”
Section: Chi3l1 In Inflammation and Cancermentioning
confidence: 99%
“…After extravasation, colonization and outgrowth in the parenchyma of distant organs are the following steps. A common theme of the metastatic process is settlement of disseminated tumor cells (DTCs) into latency (dormancy), which can last from several months to decades (11). It has been observed that DTCs are recruited into pre-metastatic niches that support their survival by interactions with endothelial, myeloid cells, fibroblasts and other types of cells.…”
mentioning
confidence: 99%